Трехмерная модель формирования залежей углеводородов на cеверо-западе Томской области; Нефтяное хозяйство; № 9 - Зубков В. А. Владимир Андреевич; Молодых П. В. Павел Владимирович; Самойленко В. В. Вадим Валерьевич; Обласов Н. В. Николай Владимирович; Ахтемийчук В. И.; Гончаров И. В. Иван Васильевич (2020, 2020)
Заглавие с экрана